2001
DOI: 10.1097/00000658-200106000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Role of Matrix Metalloproteinases in Colorectal Carcinogenesis

Abstract: ObjectiveTo measure coexpression of matrix metalloproteinase (MMP)-2, MMP-7, and MMP-9 genes by real-time quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR) in benign and malignant phases of colorectal carcinogenesis. Summary Background DataMatrix metalloproteinases degrade and remodel the extracellular matrix and have been implicated in facilitating carcinoma cells to invade and metastasize. MMP-2, MMP-7, and MMP-9 have been shown to be overexpressed in various carcinomas; however, simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
7

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 20 publications
1
47
0
7
Order By: Relevance
“…4) Further, MMP-7 expression has been detected in various neoplastic tissues, including colorectal, 5) gastric, 6) breast, 7) pancreatic, 8) and esophageal 9) cancer tissues, with the level of expression in colorectal cancers known to be significantly correlated with clinicopathological characteristics, while a reverse association with 5-year patient survival rate has been shown. 10) Of interest, Heslin et al found that the level of MMP-7 expression in colorectal adenoma was about 50-fold greater than in normal mucosa, 5) and Wilson and co-workers reported that intestinal tumor numbers and size in MMP-7 deficient Min/+ mice decreased by 58% and 20% respectively as compared with those in MMP-7…”
Section: )mentioning
confidence: 98%
“…4) Further, MMP-7 expression has been detected in various neoplastic tissues, including colorectal, 5) gastric, 6) breast, 7) pancreatic, 8) and esophageal 9) cancer tissues, with the level of expression in colorectal cancers known to be significantly correlated with clinicopathological characteristics, while a reverse association with 5-year patient survival rate has been shown. 10) Of interest, Heslin et al found that the level of MMP-7 expression in colorectal adenoma was about 50-fold greater than in normal mucosa, 5) and Wilson and co-workers reported that intestinal tumor numbers and size in MMP-7 deficient Min/+ mice decreased by 58% and 20% respectively as compared with those in MMP-7…”
Section: )mentioning
confidence: 98%
“…Many studies have shown the associations of MMP-2 and/or MMP-9 with invasion and metastasis in a variety of cancers, such as nasopharyngeal carcinoma (17), and head and neck carcinomas (33). Similarly, in CRC high expression of MMP-2 and MMP-9 may be important in tumor initiation (34,35), development (36), progression, and metastasis (37). Thus, high expression of MMP-2 and MMP-9 may be used to characterize the behaviors of colorectal carcinoma (38,39).…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 99%
“…The elevation of MMP-9 is associated with an invasiveness of colorectal cancer. A successive increase of tissue expression of MMP-2, -7 and -9 relates with an increase of malignancy -from mucous lesions and adenomas to carcinomas (13).…”
Section: Discussionmentioning
confidence: 99%
“…This could be the explanation of malignancy invasiveness mechanism. The same mechanism of extracellular matrix (basement membrane) degradation occurs at initiation of angiogenesis, which is crucial for growth of tumour mass (13,26).…”
Section: Discussionmentioning
confidence: 99%